(untitled) (Research, Society and Development, 2019)
The purpose of this study is to propose the creation of a drug organization box for elderly people with chronic noncommunicable diseases (NCDs) who are accompanied by a multiprofessional team in a health promotion area of Vale do Taquari, Rio Grande do Sul, Brazil . This study is descriptive, exploratory and qualitative approach, through groups offered by the multiprofessional team, to the elderly with CNCD, stimulating each one to develop his medicine separation box. With this project, it is expected to know the medications in use by the elderly with DCNT accompanied by the EVB, to identify the prevalent chronic diseases in the group of clients followed, to guide the elderly about the correct use of the drugs and to hold workshops to make the box organizer described for the public. With this action, the drug organization is pursued with its resolve, and the quality of life of the elderly is favored. Nursing care includes responsibility to those who for some reason can not temporarily take care of themselves, it is in this perspective that it is worth creating ways to facilitate home care.